Reproductive biology of Brycon henni (Teleostei: Bryconidae) and conservation strategies for the Nare and Guatapé rivers, Magdalena River Basin, Colombia. - Mancera-Rodríguez, Néstor Javier (Revista de Biología Tropical, 2017)
Fish can modify features of their life histories through evolutionary mechanisms to ensure the maintenance of their populations in response to environmental changes and/or fishing pressure. The reproductive biology of characid fish B. henni, in the Nare and Guatapé Rivers, Magdalena River Basin, Colombia was studied, and suggestions for conservation are presented. Ten field samplings were carried out between October 2007 and February 2012, in periods of rain, dry, transition from rain to dry and transition from dry to rain. A total of 848 specimens were collected, 360 of which were females, 441 males and 47 indeterminate. Males predominated in the catches, and the sex ratio of 1.00: 0.82 deviated significantly from the theoretical distribution 1:1. The average size captured for the total number of individuals studied was 121.5 mm SL (38.5-304.0 mm), with 133.1 mm SL for females (53.5-304.0), and 116.9 mm SL (38.5-232.5) for males. Based on the monthly variation of the gonadosomatic index (GSI) and the proportion of mature specimens, the spawning season occurs during periods of highest water levels in the rainy season. The lower values of hepatosomatic index HSI that coincide with the maximum values of the GSI, suggest that liver substances are transferred during the maturation of the ovary. The mean size at sexual maturity (L50) of B. henni was 171.5 mm SL in females, and 132.6 mm SL in males. The fecundity varied from 655 to 8 213 oocytes/female (mean= 2 072, SD= 1 648) and relative fecundity was 16.1 oocytes / g of total weight (SD= 5.9). The diameter of the oocytes was 1.24 mm (SD= 0.23). A similar development was observed in all oocytes, suggesting massive spawning activity concentrated in short periods of time. The protection of creeks and riparian habitats is a conservation priority, and protected areas such as fluvial nature reserves should be created to guarantee the survival of this species. Environmental education activities, along with water decontamination should be developed. For natural populations of B. henni is recommended to establish a minimum catch size of 270 mm SL (300 mm TL) combined with closed fishing seasons during periods of reproduction.